2021
DOI: 10.1021/acs.jpcb.1c06108
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydration in Magnesium versus Calcium Ion Pairing with Carboxylate: Solution and the Aqueous Interface

Abstract: The binding of group II metal cations such as Ca2+ and Mg2+ has been largely categorized as electrostatic or ionic using carboxylate symmetric and asymmetric stretching frequency assignments that have been historically used with little regard for the solvation environment of aqueous solutions. However, given the importance of these cations and their binding mechanisms related to biological function and in revealing surface enrichment factors for ocean to marine aerosol transfer, it is imperative that a deeper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 89 publications
0
23
1
Order By: Relevance
“…25 For the 100 mM NaCl solution, metal ions have been shown via infrared reflectionabsorption spectroscopy to alter the hydration of the carboxylate headgroups. 2,27,30,39 The PA headgroup can undergo two types of Na + coordination, either binding to one oxygen or both oxygen atoms of the PA headgroup. Spatial distribution functions were reported in literature explaining these potential sodium interactions with PA. 25 It has been shown that PA interacts with one or two Na + , and these differences in coordination could elucidate the anomalous thermodynamic values of 3D to 2D spreading we are observing in the 100 mM NaCl system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…25 For the 100 mM NaCl solution, metal ions have been shown via infrared reflectionabsorption spectroscopy to alter the hydration of the carboxylate headgroups. 2,27,30,39 The PA headgroup can undergo two types of Na + coordination, either binding to one oxygen or both oxygen atoms of the PA headgroup. Spatial distribution functions were reported in literature explaining these potential sodium interactions with PA. 25 It has been shown that PA interacts with one or two Na + , and these differences in coordination could elucidate the anomalous thermodynamic values of 3D to 2D spreading we are observing in the 100 mM NaCl system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…54 Studies that followed showed that the PA−Na + interactions help stabilize the air−water interface. 2,34 Additionally, fatty acids like PA have been abundantly sourced from marine algae, 63 undergo temporal fluctuations in enrichment at the air−seawater interface, 64 and contribute to ice nucleating particle (INP) counts. 35,65,66 65 Additionally, ESP has been used as a tool for thermodynamic consideration pertaining to ice nucleation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations